Identification of Diagnostic Biomarker for Hepatocellular Carcinoma: A Proteomic Approach - Katare, Dr. Deepshikha Pande (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Hepatocellular carcinoma (HCC), a slow multistep process eventually starts from long-term inflammation to fibrosis and leads to malignancy. These variations cause several genes disrupted that play role many signaling pathways involved in HCC. Early diagnosis and treatment of hepatocarcinogenesis depend on efficient biomarker discovery. To date, only two specific markers of HCC are identified, AFP and AFP-L3, but assessment and validation of these markers are still left in large cohorts of patients. Proteomic approach aids to develop new promising biomarker for diagnosis liver cancer at early stage. Materials and Methods: Animal model of HCC was developed. Histopathological and biochemical estimations were performed during disease progression. Proteomic analysis was done for the identification of biomarker at early stage. Results: cAMP-dependent protein kinase inhibitor alpha (PKIA) was identified using one-dimensional electrophoresis (1DE) and 2DE followed by matrix-assisted laser desorption and ionization time-of-flight mass spectrometry. Conclusion: The present study concludes the identification of potential biomarker, cAMP-dependent PKIA. It was hypothesized that PKIA is useful for detection of HCC at initial stage.